46.0k views
23 votes
Solve for x.
3(x - 4) = 2x + 6
ΟΑ. Ο
B. 2
C. 3.6
D. 10
E. 18

User Bigjim
by
4.4k points

2 Answers

6 votes

Answer:

x = 18

Explanation:

3(x-4) = 2x+6

3x-12 = 2x +6

Add 12 to the -12 and the 6, giving you...

3x = 2x + 18

subtract 2 from the 3 and the 2, giving you...

1x = 18

divide the 1 and the 18 by 1, giving you...

x = 18

I hope this helps you out!

User Supawat Pusavanno
by
5.2k points
5 votes

Answer:

the answer is D. 10

Explanation:

you get 3x -4 = 2x +6

you then subtract 2x from 3x and 2x

you get 1x - 4= 6

add 4 to both sides and you get

1x = 10 which is the same as x = 10

User Egidiocs
by
4.6k points